Pengaruh hidden curriculum dalam Pembentukan karakter Religius peserta didik di SMK Islam Lukman Al Hakim Kabupaten Bogor - Khoda, Siti (TARBAWI : Jurnal Pendidikan Agama Islam, 2023)
In an era of increasingly advanced technology, more and more information is easily accessible to students, so that students in schools, especially vocational schools, experience many difficulties in forming religious characteristics. Seeing the phenomenon of degradation that occurs in education in Indonesia today, it is necessary to take the role of an appropriate education curriculum in order to overcome these problems.The focus of the problem in this study is the effect of implementing the hidden curriculum in the formation of the religious character of students in SMK. Researchers limit the problems that will be the object of research at SMK Islam Lukman Al Hakim. This study aims to determine the implementation of the hidden curriculum at SMK Islam Lukman Al Hakim. The approach used in this research is filed research. Researchers searched for data based on interviews, questionnaires, and reviewed documents and FGDs related to the research focus. Data analysis was performed using descriptive analysis and triangulation methods.The results found by the researcher were that the effect of the implementation of hidden curriculum activities at SMK Islam Lukman Al Hakim had a positive influence on the formation of the religious character of students. Hidden curriculum is a driving force to achieve national education goals. The form of hidden curriculum activities in the formation of religious character which is carried out in SMK is an activity of habituation, exemplary and advice and motivation given by teachers to students. This becomes the basis for formulating the concept of hidden curriculum in the moral development of students in junior high schools, among others, by mapping the moral problems of students in junior high schools, making policies, making strategies, planning activities and conducting ongoing evaluations